If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x-30=-16-12x
We move all terms to the left:
5x-30-(-16-12x)=0
We add all the numbers together, and all the variables
5x-(-12x-16)-30=0
We get rid of parentheses
5x+12x+16-30=0
We add all the numbers together, and all the variables
17x-14=0
We move all terms containing x to the left, all other terms to the right
17x=14
x=14/17
x=14/17
| 4(x+1)=2(3x−2) | | v/4=1 | | 7x^2-32x-15=(7x+3) | | 6m+5(4m+8)=m+15 | | n/7+57=65 | | 25-4t=1 | | 15b=7b+8 | | 6y-20=5 | | -3.2=x-6.2 | | 20k=5k+60 | | -6(5+6x)=-6x | | 10+4=6y | | f−98=95 | | 5(n+11)=85 | | 10t-4=5t+1 | | 3+4z=11 | | 7a=a+6 | | 6k+31=-6k-6(-2k-6) | | 5y+35=5 | | 5b-3=2b | | -25y+13=38 | | E^(3x)-6=150 | | -3x+53+11x+21=90 | | 10(g-86)=8 | | 6y=30-12 | | 2t-5=t-2 | | b^2+28b-27=23 | | -8y-20=4 | | 16x-16=90 | | y=-2(1)^2-4(1) | | 2b+1=3b | | y=-2(1)^2-4(1 |